Experimental phase function and degree of linear polarization of cometary dust analogues. Issue 2 (12th January 2019) - Frattin, E; Muñoz, O; Moreno, F; Nava, J; Escobar-Cerezo, J; Gomez Martin, J C; Guirado, D; Cellino, A; Coll, P; Raulin, F; Bertini, I; Cremonese, G; et al.
Abstract: We present experimental phase function and degree of linear polarization curves for seven samples of cometary dust analogues namely: ground pieces of Allende, DaG521, FRO95002, and FRO99040 meteorites, Mg-rich olivine and pyroxene, and a sample of organic tholins. The experimental curves have been obtained at the IAA Cosmic Dust Laboratory at a wavelength of 520 nm covering a phase angle range from 3° to 175°. We also provide values of the backscattering enhancement for our cometary analogue samples. The final goal of this work is to compare our experimental curves with observational data of comets and asteroids to better constrain the nature of cometary and asteroidal dust grains. All measured phase functions present the typical behaviour for $μ$ m-sized cosmic dust grains. Direct comparison with data provided by the OSIRIS/Rosetta camera for comet 67P/Churyumov–Gerasimenko reveals significant differences and supports the idea of a coma dominated by big chunks, larger than one micrometer. The polarization curves are qualitatively similar to ground-based observations of comets and asteroids. The position of the inversion polarization angle seems to be dependent on the composition of the grains. We find opposite dependence of the maximum of the polarization curve for grains sizes in the Rayleigh-resonance and geometric optics domains, respectively.